Presence of Candida spp. in infants oral cavity and its association with early childhood caries - Fabíola Galbiatti Carvalho; Thaís Manzano Parisotto; Josimeri Hebling; Luis Carlos Spolidorio; Denise Madalena Palomari Spolidorio (Universidade Estadual de Campinas, 2016)
Candida spp., mainly C. albicans, colonizes oral cavity of infants. Transmission by mother to childbirth, pacifier use, feeding habits and caries are factors related to Candida oral colonization. Some researches related that early childhood caries favor the oral colonization of C. albicans. The present literature review described the presence of Candida spp. in oral cavity of infants and its association with early childhood caries (ECC). The literature was searched for original papers relating Candida, pacifier and baby bottle usage and ECC. The articles were selected using Bireme and Medline databases. Manual tracing of references cited in key papers was also elicited. It can be concluded that Candida spp. colonization in the infants' oral cavity, especially C. albicans, can be related to the pacifier usage, feeding habits and caries lesions. The early childhood caries favor the C. albicans colonization, although it's role in the carious process need further studies to be elucidate scientifically.